Numerical Analysis and Optimization of Displacement of Enclosure Structure Based on MIDAS Finite Element Simulation Software - Guansheng Han; Youjian Zhang; Jiqing Zhang; Haibin Zhang (Buildings)
The use of envelope structures is crucial in enhancing the safety and stability of foundation pits. However, excavation activities in the foundation pit can result in deformations affecting the envelope structure. To investigate the impact of the excavation process on the envelope structure and surrounding soil, the Midas GTS NX 2022R1 (64-bit) finite element software was employed to model the excavation process of Nantong East Railway Station. The settlement of the soil around the envelope structure and the horizontal displacement of the underground diaphragm wall (UDW) were compared with field measurements. The analysis demonstrated that the numerical analysis results exhibited a similar trend to the data obtained from field monitoring. This comparison provided valuable insights for selecting an optimal excavation method for the foundation pit and offered guidance for addressing similar challenges in the future. Additionally, a new method using metamaterials as a frame to improve the stability of continuous walls is proposed. The method relies on the excellent mechanical properties of metamaterials, improves the integrity and stability of the underground diaphragm wall, and provides a new way to solve the stability problem of underground diaphragm walls.